Effect of a multiple freeze-thaw process on structural and foaming properties of individual egg white proteins. (1st August 2017) - Duan, Xiang; Li, Junyi; Zhang, Qinjun; Zhao, Tong; Li, Mei; Xu, Xueming; Liu, Xuebo
Highlights: A freeze-thaw process varified sulfhydryl/disulfide interchange and surface hydrophobicity of albumen proteins. A freeze-thaw process resulted in protein partial denaturation, dissociation and aggregation. A freeze-thaw process enhanced foaming properties of individual albumen proteins and whole egg white. Abstract: In this study, major albumen proteins (ovalbumin, ovomucoid, ovotransferrin, lysozyme and ovomucin) were singly subjected to a multiple freeze-thaw process, and the resulting changes in structural characteristics and foamability were investigated. Structural changes of proteins occurred during the process, regarding by sulfhydryl-disulfide interchange and exposure of hydrophobic groups. The differential scanning calorimetry and scanning electron microscopy showed that these albumen proteins underwent denaturation, dissociation and possibly aggregation. Correspondingly, the foaming ability of albumen proteins improved after the freeze-thaw treatment, except for ovalbumin. The foaming ability of whole egg white was higher than that of each albumen protein, and improved after the multiple freeze-thaw process. This study extended knowledge of the relative contribution of each albumen protein to foaming properties of whole egg white during a freeze-thaw process, and suggested that a multiple freeze-thaw process is a promising technique for improving foaming properties of egg white proteins.